Divergent impacts of tocilizumab and colchicine in COVID‐19‐associated coagulopathy: the role of alpha‐defensins. (27th October 2021) - Abdeen, Suhair; Abu‐Fanne, Rami; Bdeir, Khalil; Maraga, Emad; Higazi, Mohamed; Cines, Douglas B.; Heyman, Samuel N.; Higazi, Abd Al‐Roof
Summary: Patients who are severely affected by coronavirus disease 2019 (COVID‐19) may develop a delayed onset 'cytokine storm', which includes an increase in interleukin‐6 (IL‐6). This may be followed by a pro‐thrombotic state and increased D‐dimers. It was anticipated that tocilizumab (TCZ), an anti‐IL‐6 receptor monoclonal antibody, would mitigate inflammation and coagulation in patients with COVID‐19. However, clinical trials with TCZ have recorded an increase in D‐dimer levels. In contrast to TCZ, colchicine reduced D‐dimer levels in patients with COVID‐19. To understand how the two anti‐inflammatory agents have diverse effects on D‐dimer levels, we present data from two clinical trials that we performed. In the first trial, TCZ was administered (8 mg/kg) to patients who had a positive polymerase chain reaction test for COVID‐19. In the second trial, colchicine was given (0·5 mg twice a day). We found that TCZ significantly increased IL‐6, α‐Defensin (α‐Def), a pro‐thrombotic peptide, and D‐dimers. In contrast, treatment with colchicine reduced α‐Def and Di‐dimer levels. In vitro studies show that IL‐6 stimulated the release of α‐Def from human neutrophils but in contrast to colchicine, TCZ did not inhibit the stimulatory effect of IL‐6; raising the possibility that the increase in IL‐6 in patients with COVID‐19 treated with TCZ triggers the release of α‐Def, which promotes pro‐thrombotic events reflected in an increase in D‐dimer levels.